OVARIAN RESERVE IN HEALTHY ADOLESCENT GIRLS - N.A. Buralkina; E.V. Uvarova (Union of pediatricians of Russia, 2010)
Preserving reproductive health of girls is a pressing issue for the modern healthcare industry. The purpose of this study was to determine the metrics of ovarian reserve in healthy adolescent girls aged 15 to 17 in the Republic of Mordovia. 49 healthy adolescent girls aged 15 to 17 were examined in the study. A medical and social audit was conducted at the first state to study their medical history and hereditary factors. Their physical and sexual development (sexual form, characteristic of menstrual cycle, general and gynecological exam) was assessed at the second stage. Hormonal status and ovarian reserve metrics were examined at the third stage. Ultrasonic examination of pelvic organs was conducted and concentrations of LH, FSH, estradiol and anti-Mullerian hormone (AMH) in blood were determined. The study results obtained suggest that a reduced size of ovary in girls aged 16 compared with 15-year-old girls is accompanied with the tendency toward a reduced level of AMH and increased concentration of FSH in blood serum. A significant increase in the average size of both ovaries in 17-year-old adolescents is accompanied with the tendency toward increased AMH, and, by contrast, the tendency toward a reduced level of FSH. The level of estradiol significantly increases over age, i.e. over the period from 15 to 17 years. Hence, at ages 15 and 16 all reproductive system components continue to actively adjust to cyclical functioning. By age 17, a close relationship between ovarian reserve and hormonal status is established.Key words: reproductive health, ovarian reserve, hormonal status, girls. (Pediatric Pharmacology. - 2010; 7(5):38-43)